PERSUASIVE HEDGING STRATEGIES BETWEEN NATIVE AND NON-NATIVE AUTHORS OF ENGLISH JOURNAL ARTICLES - Madya Giri Aditama (UIN Raden Mas Said Surakarta, 2018)
Writing journal articles is the most scientific way to publish new research to public. Authorsâ€™ strategies to convince the readers are important to show their stance and viewpoint on the research. This study compares the strategies chosen by native and non-native English authors of journal articles in hedging their stances. The data were hedging strategies written in 50 randomly selected international journal articles, 25 of which were written by native English authors and 25 others by the non-natives. The result shows some differences in the use of hedges. Native authors show higher frequency in the use of writer-oriented hedges whereas non-native authorsÂ had higher frequency in reader-oriented hedges. This study also finds authorsâ€™ styles to persuade the readers.